ANKYLOSING SPONDYLITIS: VALUES OF MR IMAGING - JAOVISIDHA MD, Suphaneewan; SIRIWONGPAIRAT, Pimjai; POOKARNJANAMORAKOT, Chathchai; PEKANAN, Patchrin (The ASEAN Journal of Radiology, 2023)
Two cases with ankylosing spondylitis (AS) whose MR imaging proved very helpful were reported. The first case presented with hip pain, and MR imaging was requested to clarify abnormal scintigraphic findings at femoral head-neck regions. MR imaging disclosed extensive synovitis corresponding to the known AS as well as bone marrow edema of femoral heads and necks which was an early sign of avascular necrosis (AVN). Core decompression was performed with dramatic relief of symptom. The second case had a long-standing AS, and subsequently developed colorectal carcinoma which was treated by A-P resection. He presented with back pain, abnormal spine radiographs and abnormal bone scintigram. MR imaging revealed spondylitic process and helped exclude metastasis.